Manajemen Kepemimpinan Kepala Sekolah Sebagai Administrator dalam Meningkatkan Kompetensi Pedagogik Guru - Jauhari (Economic Reviews Journal, 2024)
This study aims to (1) analyze the planning of school principals as administrators can improve teacher competence, (2) analyze the direction of school principals in improving teacher competence, (3) analyze the implementation process of school principals in improving teacher competence, and (4) analyze the supervision of the principal on the improvement of teacher competence. This study uses a qualitative method by describing the form of principal management in improving teachers' pedagogic competence. The data collection technique used is using data collection techniques by means of interviews, observations and documentation. The result of this study is that the principal in an effort to improve teacher competence which includes 1) an early year meeting to analyze teacher needs and form a program to be carried out and a year-end meeting as evaluation material. 2) Providing direction to teachers through motivation, building a comfortable atmosphere, deliberation and good communication. 3) Carry out previously agreed plans, including implementing technology guidance, making teacher training, teachers are required to teach in accordance with their fields, delegating to Teacher Working Groups (KKG), conducting classroom action research, developing a curriculum by actively involving students. (4) supervision carried out by the principal includes classroom practice routines, supervision, class visits and evaluations.